Mothers' Psychological Well-Being and the Risk of Stunting in Early Childhood - Danella Kharismatika; Idat Muqodas (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Stunting remains a major public health challenge in Indonesia, with maternal factors playing a crucial role. This study analyzes the relationship between maternal psychological well-being and the risk of stunting in early childhood. A cross-sectional study was conducted at UPTD Puskesmas Purwakarta in October 2025, involving 35 mothers of stunted children aged 0-5 years selected via purposive sampling. Psychological well-being was measured using Ryff's scale, and stunting risk was assessed via a validated questionnaire. Data were analyzed using Pearson correlation and multiple linear regression. Bivariate analysis showed a significant negative correlation (r = -0.40; p = 0.018). However, multivariate analysis controlling for maternal age, education, and occupation revealed a significant positive relationship (b= 0.31; 95% CI= 0.05 to 0.57; p=0.022), indicating a suppressor effect of education that reverses the relationship. The model explained 31.4% of the variance in stunting risk (R² = 0.314; Adjusted R² = 0.223). The findings reveal a complex relationship in which higher education reduces stunting risk but may lower maternal psychological well-being, thereby obscuring the positive association between well-being and stunting risk. Stunting prevention programs should integrate psychological support with educational interventions, focusing on stress management and reframing health information for educated mothers. Keywords: maternal psychological well-being, risk of stunting, early childhood